If α + β + γ =&nbs

Previous Year Papers

Download Solved Question Papers Free for Offline Practice and view Solutions Online.

Test Series

Take Zigya Full and Sectional Test Series. Time it out for real assessment and get your results instantly.

Test Yourself

Practice and master your preparation for a specific topic or chapter. Check you scores at the end of the test.
Advertisement

 Multiple Choice QuestionsMultiple Choice Questions

861.

If tanθ + tanθ + π3 + tanθ + 2π3 = 3, then which of the following is equal to 1 ?

  • tan2θ

  • tan3θ

  • tan2θ

  • tan3θ


Advertisement

862.

If α + β + γ = 2θ, then cosθ + cosθ - α + cosθ - β + cosθ - γ = ?

  • 4sinα2 . cosβ2cosγ2

  • 4sinα2 . sinβ2sinγ2

  • 4cosα2 . cosβ2 . cosγ2

  • 4sinα . cosβ . cosγ


C.

4cosα2 . cosβ2 . cosγ2

Now, α + β + γ = 2θ, then cosθ + cosθ - α + cosθ - β + cosθ - γ = 2cosθ - α + β2cosβ - α2 + 2cosγ2cosθ - γ2= 2cosγ2cosβ - α2 + 2cosγ2cosα + β2= 2cosγ2cosβ - α2 + cosα + β2 = 2cosγ22cosα2cosβ2= 4cosα2cosβ2cosγ2


Advertisement
863.

x  R : cos2x + 2cos2x = 2 = ?

  • 2 + π3 : n  Z 

  •  ± π6 : n  Z 

  •  + π3 : n  Z 

  • 2 - π3 : n  Z 


864.

1 + tanhx21 - tanhx2 = ?

  • e - x

  • ex

  • 2ex2

  • 2e - x2


Advertisement
865.

In ABC, if 1b + c + 1c +a = 3a +b + c, then C is equal to

  • 90°

  • 60°

  • 45°

  • 30°


866.

Observe the following statementsI In ABC, bcos2C2 + ccos2B2 = sII  In ABC, cotA2 = b + c2  B = 90°Which of the following is correct ?

  • Both I and II are true

  • I is true, II is false

  • I is false, II is true

  • Both I and II are false


867.

In a triangle, if r1 = 2r2 = 3r3, then ab + bc + ca  = ?

  • 7560

  • 15560

  • 17660

  • 19160


868.

From the top of a hill h metres high the angles of depressions of the top and the bottom of a pillar are α and β respectively.The height (in metres) of the pillar is

  • htanβ - tanαtanβ

  • htanα - tanβtanα

  • htanβ + tanαtanβ

  • htanβ + tanαtanα


Advertisement
869.

The period of sin4x + cos4x is

  • π42

  • π22

  • π4

  • π2


870.

cosxcosx - 2y = λ  tanx - ytany is equal to

  • 1 + λ1 - λ

  • 1 - λ1 + λ

  • λ1 + λ

  • λ1 + λ


Advertisement